Interpersonal sensitivity and its associated factors among nursing students during the COVID-19 pandemic: a network analysis - Xue Wang; Jie Yuan; Zirong Tian; Xinji Shi; Xu Liu; Yibo Wu; Shuang Zang (BMC Nursing)
Abstract Background Interpersonal sensitivity is a crucial individual characteristic, particularly for young nursing students. However, limited research has specifically examined interpersonal sensitivity in nursing students. This study aimed to employ network analysis to investigate the interconnectedness of interpersonal sensitivity and its associated factors among nursing students during the COVID-19 pandemic. Methods Network analysis was employed to explore the network structure. The first network model was developed to evaluate interpersonal sensitivity. The second network model was constructed to investigate the associations between interpersonal sensitivity and variables that were found to be statistically significant in the multivariable linear regression model. Results A total of 864 nursing students participated in the study. The strongest nodes in assessing interpersonal sensitivity among nursing students encompass three distinct aspects: compliments, genuine understanding, and criticism. The multivariate linear regression analysis revealed significant associations between interpersonal sensitivity and various factors, including openness (β = 0.67), anxiety symptoms (β = 0.45), well-being (β = -0.63), loneliness (β = 1.55), and perceived social support (β = 0.66). Conclusions This study yields valuable insights into the phenomenon of interpersonal sensitivity among nursing students amid the COVID-19 pandemic. These findings emphasize the significance of incorporating targeted interventions addressing these factors into nursing education curricula.